Gambaran Kinerja Instalasi Farmasi Rumah Sakit Swasta Menggunakan Metode Balaced Scorecard Dengan Perspektif Pertumbuhan dan Pembelajaran Serta Bisnis Internal - Makkulawu, Andi; Yuliana, Besse (Jurnal Literasi Mandiri, 2024)
the hospital divisions that has an inseparable part of the hospital's healthcare system which is intact and oriented to patient care, providing quality medicine, and affordable prices for all levels of society. One of the measurements that can be carried out at the aforementioned pharmacy Installation is a balanced scorecard.The objective of this study is to measure the performance of the Pharmacy Installation of the site area with a balanced scorecard approach on the perspective of growth and learning and internal business. It used a type of non-experimental research design with a descriptive approach. Further, the object of the study employed staffing data in 2018, drug inventory reports, 2019 Formulary data, and supply data for Pharmacy Installation for a sample of 7 respondents and 100 prescriptions.The results show that in the perspective of growth and learning indicators the employee turnover rate of 28% is categorized as unideal; employee satisfaction is classified as satisfied with a percentage of 57,15%, and; the employee passion category is obtained by a percentage of 71,43%. The optimal internal business perspective is the average period of drug supply, while indicators that have not been maximized are the level of drug availability, formulary compliance, and prescription of expired drugs.